Effects of Military Service on Earnings and Education Revisited - Paco Martorell,, Trey Miller, Lindsay Daugherty, Mark Borgschulte (RAND Corporation, 2014)
Policymakers and the public at large have expressed concern about the economic well-being of veterans returning home from service overseas; these concerns have grown in recent years during the economic recession. The research described in this report builds on research conducted by RAND Corporation researchers in 2011 with support from the U.S. Army (Loughran, Martorell, Miller, and Klerman, 2011). They estimated that, for as many as 18 years following enlistment, the causal effect of military service on labor market earnings and on a critical determinant of earnings, educational outcomes. They addressed the empirical problems associated with the selective nature of military service by restricting their analysis to military applicants, some of whom enlist and some of whom do not, and by controlling for a rich array of applicant characteristics available on the military application record. They found that military enlistment increases earnings in both the short and long terms, although there is a large dip in earnings in the period immediately following separation from military service. Enlistment delays college education and decreases the likelihood of obtaining a four-year college degree but increases the likelihood of obtaining a two-year degree. This report addresses some possible driving forces behind those returns, outside factors that could also affect them, and the potential for the military to directly affect postmilitary earnings. The goal of this research, supported by the Office of the Secretary of Defense, was to extend the work, honing in on the earnings dip and disaggregating the data to look at differences in earnings and education depending on a service member’s length of service, military occupational specialty while in the service, and labor market conditions present at the time of separation from military service. We also analyzed the effect on earnings of an Army recruiting program called Partnership for Youth Success. This research will be of interest to the U.S. Department of Defense, the U.S. Department of Veterans Affairs, and policymakers who have responsibility for recruiting, setting appropriate compensation, and developing programs that help veterans make the transition from military to civilian life. It will also be of interest to researchers interested in the return to military service and the experiences of service members who transition to civilian life. This research was sponsored by the Office of Accession Policy within the Office of the Under Secretary of Defense for Personnel and Readiness and conducted within the Forces and Resources Policy Center of the RAND National Defense Research Institute, a federally funded research and development center sponsored by the Office of the Secretary of Defense, the Joint Staff, the Unified Combatant Commands, the Navy, the Marine Corps, the defense agencies, and the defense Intelligence Community.